The environmental crisis--opposing viewpoint - Bernards, Neal (San Diego, Calif. : Greenhaven Press, 1991)
Presents opposing views on questions of environmental protection and damage resulting from air and water pollution, toxic wastes, pesticides and the ever-growing tide of refuse
Keywords: Environmental policy -- United States; Environmental protection